Research handbook on transnational environmental law - Heyvaert, Veerle; Duvic-Paoli, Leslie-Anne (Research handbooks in environmental law, 2020)
"This illuminating Research Handbook offers a detailed overview and critical discussion of the key themes and perspectives that characterize the burgeoning research area of transnational environmental law. It analyzes important sectors at the forefront of the field, including climate change and biodiversity. Interdisciplinary and comprehensive, this Research Handbook provides stimulating and provocative discussions on transnational legal phenomena and the ways in which we can unpack their complexities. Bringing together varied perspectives from both leading and emerging scholars from around the world, chapters deliver methodological and conceptual frameworks for future research, whilst providing an original view on this emerging field of law. Contributors also pay special attention to the engagement of the field with multilevel governance and the involvement of non-state actors in legislative, regulatory and adjudicative processes. Offering an accessible and broad-ranging guide to the field's major themes and research strategies, the Research Handbook on Transnational Environmental Law will be an indispensable resource to scholars, students and practitioners in environmental and transnational law and social sciences seeking to understand the contributions of a transnational approach to environmental law"--